The Effect of Financial Performance, Audit Committee, And Sharia Supervisory Board On Return On Assets (Sharia Commercial Banks) - Faisal, Mohamad; Rosidi (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2025)
This study aims to analyze the effect of operational costs on operational income (BOPO), financial to deposit ratio (FDR), capital adequacy ratio (CAR), productive asset quality (KAP), minimum statutory reserve (GWM), audit committee (KA), and sharia supervisory board (DPS) on the return on assets (ROA) of Islamic commercial banks. Using quantitative analysis, this study involves 48 samples from 8 Islamic commercial banks over the 2017-2022 period, selected using the purposive sampling method. Based on agency theory and fundamental analysis, the study finds that FDR has a positive effect on ROA, while BOPO and KAP have a negative effect. However, this study fails to prove the effect of CAR, GWM, KA, and DPS on the ROA of Islamic commercial banks.